2015
DOI: 10.4184/asj.2015.9.3.407
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Scoliosis Screening in Nara City Schools: A 23-Year Retrospective Cross-Sectional Study

Abstract: Study DesignRetrospective cross-sectional study.PurposeTo determine the prevalence of idiopathic scoliosis, define the distribution of the curve magnitude, evaluate the accuracy of Moiré topography as a screening tool, and investigate the cost-effectiveness of our screening system.Overview of LiteratureEarly detection of idiopathic scoliosis provides the opportunity for conservative treatment before the deformity is noticeable. We believe that scoliosis screening in schools is useful for detection; however, sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 19 publications
1
20
0
1
Order By: Relevance
“…This finding was higher than previously reported PPV for scoliosis screening in Malaysia by Htwe et al 6 . We also found that our school screening programme was more predictive than other Asian country such as Singapore (27.5% - 47.7%) 1 , Korea (41.0% - 51.0%) 4 , China (33.8% -43.2%) 10 , and Japan (33.3%) 9 . Only the school screening programme done in Hong Kong 3 , 8 had a higher PPV than our study (76.5% - 81.0%).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This finding was higher than previously reported PPV for scoliosis screening in Malaysia by Htwe et al 6 . We also found that our school screening programme was more predictive than other Asian country such as Singapore (27.5% - 47.7%) 1 , Korea (41.0% - 51.0%) 4 , China (33.8% -43.2%) 10 , and Japan (33.3%) 9 . Only the school screening programme done in Hong Kong 3 , 8 had a higher PPV than our study (76.5% - 81.0%).…”
Section: Discussionsupporting
confidence: 57%
“…The percentage of students diagnosed of scoliosis amongst those positively screened is known as the positive predictive value (PPV). Amongst the Asian countries, the PPV of school scoliosis screening ranged from 20% to 70% 1 , 3 , 4 , 6 , 9 - 11 . A previous study done in Malaysia has reported a PPV school scoliosis screening of 35.7% with a small study population of 832 students 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Some reports recommend the scoliometer; however, there are issues, such as its weak correlation to the Cobb angle or the need for the rater to perform the forward bend or manual data measurement within a limited time [5][6]15]. MT also shows a high rate of false positives, at 35%-67% [8][9]. However, in Japan, it has continued to be widely used since the 1980s in some regions to this day as an objective method of screening [8].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional Moiré topography (MT) is a method of evaluating the shape of the trunk based on the external body contour [7]. However, a limitation of MT is the high rate of false positives at 35%-67%; yet, it continues to be used in certain regions in Japan for examination [8][9]. The production of cameras for MT (FM40SC, made by Fujifilm Medical, Japan) was discontinued 10 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies conclude that there is not enough evidence either way to come to a conclusion regarding the benefit of school scoliosis screening, and that further evidence is needed before drawing conclusions (5, 13, 1921). Our paper provides similar indeterminate findings regarding the benefit of school screening.…”
Section: Discussionmentioning
confidence: 99%